An investigation of shippers’ satisfaction and behaviour towards corporate social responsibility in maritime transport - Wong, Yiik Diew (2019)
Anchoring on the theory of planned behaviour (TPB), the current paper investigates the moderating influences of shippers’ corporate social responsibility (CSR) beliefs on their satisfaction and behaviour towards shipping firms’ involvement in CSR. It also analyses organisational and environmental factors that shape shippers’ CSR beliefs. Survey data were obtained from 276 shippers with business offices located in Singapore, and analysed using multi-sampling approach and linear regression modelling. The results show that shippers with strong CSR beliefs derive greater satisfaction, and exhibit stronger behavioural intentions towards shipping firms’ involvement in CSR. In addition, shippers’ CSR beliefs are influenced by shippers’ organisational characteristics such as (1) firm’s age, (2) firm’s size, (3) degree of internationalisation, (4) types of products shipped, and environmental factors such as (5) perceived environmental and social threats, (6) perceived level of competition, and (7) level of CSR practices in headquarters. The results contribute to TPB research application in both B2C and B2B contexts, and motivate changes to the current marketing and communication practices of shipping firms.